THE INFLUENCE OF WORK ENVIRONMENT, WORK MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE SATISFACTION - Ali, Mukti; Ningrum, Anggung Prasetya (Universitas Maarif Hasyim Latif, 2024)
Human Resources (HR) are an important component that influences the development of a company, and have differentfunctions from the organizational or company structure and human resources are directly influenced by the workenvironment that makes employees feel comfortable and employees receive support that makes them feel good support.This comes from co-workers and is appreciated directly from the leadership for the work that has been done andemployees must comply with the rules that have been made and not violate them and employee satisfaction will befulfilled if human resources are wiser and are properly cared for by the organization, company or agency. This researchaims to determine and analyze the influence of the work environment, work motivation and work discipline on employeesatisfaction at the Mojokerto Regency National Land Office. The population in this study was 155 with a saturatedsampling technique sample of 65 respondents. The data analysis method uses respondent characteristics testing, TCRtesting (respondent achievement level), validity testing, reliability testing, classical assumption testing, measurementmodel testing, correlation testing, multiple linear regression analysis testing and hypothesis testing. The research resultsshow that Hypotheses H1, H2, H3, H4, H5, H6 are accepted, which means that the work environment variables, workmotivation and work discipline partially influence employee satisfaction with a significance level < 0.05 and t count >t table (1.99962) , where of the three variables, the variable with the most dominant partial influence is the workenvironment with a beta coefficient value of 11.447. The results of the research hypothesis H7 show that it is acceptable,which means that the variables of work environment, work motivation and work discipline simultaneously influenceemployee satisfaction with a significance level of 0.001 < 0.05.